2021
DOI: 10.1111/dme.14568
|View full text |Cite
|
Sign up to set email alerts
|

Mortality in 98 type 1 diabetes mellitus and type 2 diabetes mellitus: Foot ulcer location is an independent risk determinant

Abstract: Introduction:We previously demonstrated in both a longitudinal study and in metaanalysis (pooled relative-risk RR, 2.45) that all-cause mortality is significantly higher in people with diabetes foot ulceration (DFU) than with those without a foot ulcer. In this prospective study, we looked at the factors linked to mortality after presentation to podiatry with DFU. Methods: Ninety-eight individuals recruited consecutively from the Salford Royal Hospital Multidisciplinary Foot Clinic in Spring 2016 were followed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…Previous studies have reported that renal failure is closely associated with DFU mortality ( 25 ). Notably, A prospective study showed that 40% of patients died during the follow-up period, 35% of those due to renal failure ( 33 ). In our study, a total of 7 cases died from CKD with hemodialysis, which similarly suggested that CKD contributed much to mortality of DFUs patients.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that renal failure is closely associated with DFU mortality ( 25 ). Notably, A prospective study showed that 40% of patients died during the follow-up period, 35% of those due to renal failure ( 33 ). In our study, a total of 7 cases died from CKD with hemodialysis, which similarly suggested that CKD contributed much to mortality of DFUs patients.…”
Section: Discussionmentioning
confidence: 99%
“…The mid-trial visits are missed if the following cannot be fulfilled: (1) The visit is within a window of ±7 days; and (2) The visit is minimum 2 weeks after the previous trial visit. The window for the 20-week visit is from 20 weeks to 22 weeks and 4 days after baseline.…”
Section: Trial Schedulementioning
confidence: 99%
“…Chronic foot ulcers affect the quality of life of people with diabetes widely and is associated with increased mortality and morbidity. [1][2][3][4][5] Of people with diabetes 15%-25% develop chronic foot ulcers during their lifetime, 50%-60% of diabetic foot ulcers (DFUs) become infected and 20% of patients with infected DFUs undergo lower extremity amputations. 2 3 6 The treatment of these hard-to-heal ulcers is challenging.…”
Section: Introductionmentioning
confidence: 99%
“…In the first, 98 people with diabetes and active foot ulceration were followed up over 2 years. 1 Forty percent of the cohort died during follow-up, emphasising the enormous mortality of foot ulceration for people with diabetes. This alone is a striking and sobering finding but the authors also report that hindfoot ulceration has a sixfold greater risk of death compared with forefoot, independent of other factors, and the type of ulcer (ischaemic, neuropathic or both) had no impact on mortality.…”
mentioning
confidence: 99%
“…In the first, 98 people with diabetes and active foot ulceration were followed up over 2 years 1 . Forty percent of the cohort died during follow‐up, emphasising the enormous mortality of foot ulceration for people with diabetes.…”
mentioning
confidence: 99%